On Maxwell Equations with the Transparent Boundary Condition (Journal of Computational Mathematics, 2018)
In this paper we show the well-posedness and stability of the Maxwell scattering problem with the transparent boundary condition. The proof depends on the well-posedness of the time-harmonic Maxwell scattering problem with complex wave numbers which is also established.
Keywords: Electromagnetic scattering; Well-posedness; Stability.